PERANCANGAN APLIKASI ONLINE SHOP NEWS BERBASIS MOBILE DAN WEBSITE - Foris Julio Suyanto; Tony Tony; Bobby Tumbelaka (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Distributed System Development At Toko Emas Makmur  Based On Desktop and Web Applications is an application used to allow users to store to report all transactions and data items. This application uses three (3) platforms, the Desktop and Web applications are distributed using the Web Service. This application was built using Visual Studio 2015 software on desktop and web applications, as well as SQL Server 2015 as the database of the program. This application involves three (3) the results of which will be a report that sales transactions, purchase transactions, and Data Products. This application uses the UAT (User Aceptence Test), and Blackbox testing in the testing process. From the testing that has been done shows that desktop applications can be connected or properly distributed to the web through the Web Service.